Desarrollo de la capacidad autorreguladora en ambientes hipermediales durante la consulta de información y su relación con el logro del aprendizaje. - Gómez Oviedo, Mónica (Universidad Antonio Nariño, 2023)
In this thesis, the development of self-regulatory capacity in a computer-based learning environment is studied during information consultation, which are carried out by cycle 3 education students and from interaction with a hypermedia environment, on topics of the natural sciences curriculum. To carry out this study, a strategy based on four elements of self-regulation was designed: planning, analysis, interpretation and evaluation. The research involved 26 students who were randomly distributed into two groups, a control group and an experimental group, and who were part of a private educational institution called the ¨del Bosque Bilingüe¨ school, which is located in the town of Suba, in the city of Bogotá.